2012
DOI: 10.1002/hbm.22160
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right hemisphere in metaphor comprehension: A meta-analysis of functional magnetic resonance imaging studies

Abstract: The role of the right hemisphere (RH) in metaphor comprehension is still controversial. Numerous neuroimaging studies have found that conventionality, sentential context, and task demand can influence the involvement of the RH in metaphor processing. The current meta-analysis used foci from 17 original functional magnetic resonance imaging studies to identify what factors modulate the involvement of the RH in metaphor processing. Activation likelihood estimation was used for quantification. We focused on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 73 publications
7
64
2
3
Order By: Relevance
“…Several studies indicate that processing novel metaphors shows stronger effects only in the left brain regions compared with literal processing (e.g., Mashal et al, 2009;Rapp et al, 2004;Schibata et al, 2007). A recent metaanalysis using activation likelihood estimation found that the significant effects in the right hemisphere during metaphor processing occur when the metaphorical meaning is novel (Yang, 2012). This result supports the right hemisphere hypothesis on processing broad semantic fields and integrating distant concepts (Beeman, 2005).…”
Section: Figurative Language Comprehensionsupporting
confidence: 50%
“…Several studies indicate that processing novel metaphors shows stronger effects only in the left brain regions compared with literal processing (e.g., Mashal et al, 2009;Rapp et al, 2004;Schibata et al, 2007). A recent metaanalysis using activation likelihood estimation found that the significant effects in the right hemisphere during metaphor processing occur when the metaphorical meaning is novel (Yang, 2012). This result supports the right hemisphere hypothesis on processing broad semantic fields and integrating distant concepts (Beeman, 2005).…”
Section: Figurative Language Comprehensionsupporting
confidence: 50%
“…Therefore, individual concepts are less specific; some of the discriminating factors between concepts are forfeited in exchange for access to a larger semantic network. Coarse semantic processing is thought to play an important role in inference making (Beeman, 1993;Beeman, Bowden, & Gernsbacher, 2000), metaphor processing (Yang, 2014), reading (St. George, Kutas, Martinez, & Sereno, 1999;Sandak, Mencl, Frost, & Pugh, 2004), idiom processing (Yang et al, 2016), and insight (Bowden & Beeman, 1998).…”
Section: Narrow Versus Coarse Semantic Processingmentioning
confidence: 99%
“…These masks were mirror-projected onto the right hemisphere (RH) to create six homologous masks (the masks cover significant parts of the cortex, so their mirrored version is likely to encompass the righthemispheric homologue of the left-hemispheric language network, despite possible hemispheric asymmetries in their precise locations). These RH homologues were included because they are activated during many language-processing tasks (54,(114)(115)(116)(117) and they show strong functional correlations with the LH language network during naturalistic cognition (59). In each of the resulting 12 masks, a fROI was defined using the top 10% method described in the Methods section of the main text.…”
Section: Supplementary Materialsmentioning
confidence: 99%